The Effect of Nutrition Education Intervention Towards Nutritional Behavior of Mother In Stunting Children: A Systematic Review - Karra, Aulya Kartini Dg; Arief, Yuni Sufyanti; Probowati, Ririn (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Stunting has become a global concern in the last decades, several studies have shown that one of the main causes of stunting is based on the knowledge of the mother. The aim of this study is the effect of nutrition education interventions on maternal nutritional behavior in stunted children. This method of compiling a systematic review is based on literature studies from various electronic databases, including Scopus, ProQuest, Science Direct, EBSCO, ResearchGate, and Google Scholar by conducting a review using the latest PRISMA. The keywords in this systematic study were unbeatable with the Medical Subject Heading (MeSH) consisting of (Maternal behavior OR maternal behavior AND nutrition education AND Growth Disorders OR stunting). 10 articles fit the inclusion criteria, the main results of the articles discuss maternal nutritional behavior. Appropriate nutrition education interventions are effective to prevent and improve the status of stunting children.